2001
DOI: 10.1063/1.1404427
|View full text |Cite
|
Sign up to set email alerts
|

Current injection into high temperature superconductors: Does spin matter?

Abstract: Recent comparative studies of quasiparticle injection from colossal magnetoresistance (CMR) materials and normal metals into high transition temperature superconductors (HTS) have led several investigators to conclude that spin-polarized injection from CMR electrodes is far more efficient than ordinary injection in suppressing superconductivity. On the other hand, some ordinary quasiparticle injection experiments have shown greater suppression of superconductivity than was claimed in any of the published spin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 27 publications
0
44
1
Order By: Relevance
“…LCMO is a relatively bad metal and many collision events will result in electrons being scattered into the YBCO. These electrons will be highly spin polarized and are expected to cause T c depression by pair breaking as previously discussed by other authors [40][41][42] if the YBCO thickness is smaller than the spin diffusion length, l S . An estimate of l S in YBCO can be obtained using the relation l S = ͑l 0 v F S ͒ 0.5 , 41 where S is the spin-polarized quasiparticle diffusion time, v F is the Fermi velocity, and l 0 is the electron mean free path.…”
Section: Resultsmentioning
confidence: 81%
“…LCMO is a relatively bad metal and many collision events will result in electrons being scattered into the YBCO. These electrons will be highly spin polarized and are expected to cause T c depression by pair breaking as previously discussed by other authors [40][41][42] if the YBCO thickness is smaller than the spin diffusion length, l S . An estimate of l S in YBCO can be obtained using the relation l S = ͑l 0 v F S ͒ 0.5 , 41 where S is the spin-polarized quasiparticle diffusion time, v F is the Fermi velocity, and l 0 is the electron mean free path.…”
Section: Resultsmentioning
confidence: 81%
“…A Tc depression results over relatively long length scales in the superconductor, which has been theoretically addressed by Radovic et al [10], and experimentally observed in metallic superlattices by several groups [11][12][13]. In addition since the current is injected through the upper YBCO layer, and although current distribution may be complex in these kind of samples, we can not exclude the possibility of pair breaking by polarized quasiparticles injected into the superconductor [1][2][3]. Further work will be necessary to explore the relative importance of both contributions.…”
Section: Ferromagnetic (F) / Superconductor (S) Heterostructures Havementioning
confidence: 99%
“…2 Ferromagnetic (F) / superconductor (S) heterostructures have recently attracted much interest for applications in spin injection (three terminal) devices [1]. High Tc superconductors (HTS) and colossal magnetoresistance (CMR) oxides are interesting candidate materials because the low carrier density of the HTS and the almost full spin polarization of the CMR oxides can be combined to yield high sensitivity (gain) fast devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spin injection depletes the superconducting condensate and can result in switching to a normal state of much higher resistance (Dong et al, 1997;Vas'ko et al, 1997;Takahashi et al, 1999;Wei et al, 1999;Yeh et al, 1999). A critical review of possible spurious effects in reported experiments (Gim et al, 2001) has also stimulated the development of a novel detection technique which uses scanning tunneling spectroscopy combined with pulsed quasiparticle spin injection to minimize Joule heating (Ngai et al, 2004;see Sec. IV.A.1).…”
Section: F/n Junctionmentioning
confidence: 99%